2013
DOI: 10.4238/2013.december.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with glutamine reduces genetic damage due to cancer treatment with cisplatin

Abstract: ABSTRACT.Cisplatin is an effective antineoplastic drug. However, it provokes considerable collateral effects, including genotoxic and clastogenic activity. It has been reported that a diet rich in glutamine can help inhibit such collateral effects. We evaluated this activity in 40 Swiss Glutamine chemoprevention in vivo mice, distributed into eight experimental groups: G1 -Control group (PBS 0.1 mL/10g body weight); G2 -cisplatin group (cisplatin 6 mg/kg intraperitoneally); G3, G4, G5 -glutamine groups (glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Although there are significant differences in the frequency of micronuclei between the negative control group and the groups treated with IR-01, Vaz et al (2016) describes that this isolated fact does not necessarily imply in toxicogenetic damage. Also, according to the results observed in other experiments from our research group ( Oliveira et al , 2009a , 2013 ; Mauro et al. , 2010 ; Pesarini et al , 2014 ; Navarro et al , 2015 ), the baseline frequency of micronuclei can be greater than the frequency observed for the animals treated with IR-01 in the present study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although there are significant differences in the frequency of micronuclei between the negative control group and the groups treated with IR-01, Vaz et al (2016) describes that this isolated fact does not necessarily imply in toxicogenetic damage. Also, according to the results observed in other experiments from our research group ( Oliveira et al , 2009a , 2013 ; Mauro et al. , 2010 ; Pesarini et al , 2014 ; Navarro et al , 2015 ), the baseline frequency of micronuclei can be greater than the frequency observed for the animals treated with IR-01 in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to the ability to reduce commercial chemotherapeutics effects, IR-01 also has a pharmacophoric radical in its structure, which could increase the antioxidant defenses in non-injured cells. This hypothesis is supported by Bianchi and Antunes (1999) , Albertini and Ruiz (2001) , Antunes and Bianchi (2004) , and Oliveira et al. (2013) , who reported that cells that have DNA lesions are deficient in antioxidant defenses.…”
Section: Discussionmentioning
confidence: 77%
“…This study used pretreatment, simultaneous simple, simultaneous with pre-incubation, and post-treatment protocols to evaluate the antimutagenicity of inulin. The simultaneous simple protocol indicated the desmutagenic and bioantimutagenic activity, the simultaneous with pre-incubation protocol indicated the desmutagenic activity, and the pre-and post-treatment protocols indicated preferably a biomutagenic activity (Ferguson, 1994;Flagg et al, 1995;Antunes and Araújo, 2000;De Flora and Ferguson, 2005;Oliveira et al, 2006Oliveira et al, , 2007Oliveira et al, , 2009Oliveira et al, , 2013bda Silva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This was revealed by the damage reduction percentages of 115.05, 119.06, and 114.38% for the glutamine doses of 150, 300, and 600 mg/kg bw, respectively. Oliveira et al (2013) also tested the chemopreventive activity of glutamine using the same assays but with a different protocol. The authors also observed no dose-dependent response, but similar DR% values were observed for the comet assay.…”
Section: Discussionmentioning
confidence: 99%